2006
DOI: 10.1186/1746-1596-1-17
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Background: Epstein-Barr virus (EBV) is associated to the etio-pathogenesis of an increasing number of tumors. Detection of EBV in pathology samples is relevant since its high prevalence in some cancers makes the virus a promising target of specific therapies. RNA in situ hybridization (RISH) is the standard diagnostic procedure, while polymerase chain reaction (PCR)-based methods are used for strain (EBV type-1 or 2) distinction. We performed a systematic comparison between RISH and PCR for EBV detection, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…In another study more than 95% concordance was detected between PCR results and EBER-ISH for detection of EBV (26, 27). Leong et al (21, 28) suggested that the EBER-ISH method was the most sensitive method for EBV detection.…”
Section: Discussionmentioning
confidence: 89%
“…In another study more than 95% concordance was detected between PCR results and EBER-ISH for detection of EBV (26, 27). Leong et al (21, 28) suggested that the EBER-ISH method was the most sensitive method for EBV detection.…”
Section: Discussionmentioning
confidence: 89%
“…This corroborated findings in a Chinese study in which the rate of EBV detection in NHL was also higher (42.6%) than that of HL (26.3%), (p=0.213) [ 34 ]. Despite the fact that many studies confirm a strong association between EBV and lymphomas, the detection of EBV has not produced consistent results due to biological heterogeneity of the virus and diversity of lymphoma subtypes [ 6 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Older adults and children who are EBV-positive have a poor prognosis, possibly reflecting a poor immune status, which in turn means that these patients may tolerate the disease and its treatment less effective [ 8 ]. Making use of EBV association with lymphomas for clinical purposes and therapeutic treatment is of interest [ 9 ]. Therefore, the aim of this study was to provide evidence for the presence of EBV in lymphomas diagnosed at the University Teaching Hospital in Lusaka, Zambia.…”
Section: Introductionmentioning
confidence: 99%
“…Copy number range of 1 to 50 of EBV DNA may be detected in a healthy person infected with EBV in white blood cells (WBC) [122]. PCR and real-time PCR sensitivity and specificity vary based on detection methods as well as laboratory to laboratory practise [118, 123, 124]. …”
Section: Ebv Detection Methodsmentioning
confidence: 99%